Bone volume changes after immediate implant placement with or without flap elevation. Issue 4 (14th March 2016) - Mazzocco, Fabio; Jimenez, Daniel; Barallat, Lucía; Paniz, Gianluca; Del Fabbro, Massimo; Nart, Jose
Abstract: Objectives: The aims of this prospective study were to evaluate bone dimensions after immediate implant placement with simultaneous grafting of the buccal gap, to determine if initial buccal bone width had an influence on bone remodelling and to compare bone volume changes using a flap or a flapless approach after 6 months of healing. Material and methods: This prospective study included patients who required an extraction and a subsequent immediate implant placement at a non‐molar site. In those cases where tooth extraction was not feasible with a flapless approach (test group) a mucoperiosteal flap was carefully elevated (control group). After extraction, a cone beam computed tomography (CBCT) was taken. Then, an implant was placed and the buccal gap was grafted using anorganic bovine bone. After 6 months of healing, a second CBCT was performed. A blinded investigator superimposed both images and performed a series of measurements to determine bone volume changes between the two time points. Results: Thirty‐five patients were included in this study, 20 of which belonged to the test group. All together, the differences between baseline and 6 months in buccal plate height, lingual plate height and in ridge width at 2, 4 and 6 mm were 0.48 ± 1.35; 0.58 ± 1.51; 0.64 ± 0.81; 0.59 ± 1.36 and 0.52 ± 1.16, respectively. Only a moderate correlation was observed between initial buccal plate width and buccal plate height at 6 months ( P = 0.0001). No statistically significant differences were observed between flap and flapless approach. Conclusions: A mean reduction of around 0.5 mm in height and width after placing immediate implants and filling the residual gap with anorganic bovine bone may be expected. No significant association between initial buccal bone width and ridge width at 6 months was seen. No statistically significant differences were found between the two treatment protocols although more ridge reduction was observed for the flap group.